The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1258/td.2009.090005
|View full text |Cite
|
Sign up to set email alerts
|

High maternal mortality and stillbirth in the Wad Medani Hospital, Central Sudan, 2003–2007

Abstract: The aim of this study was to investigate the incidence and causes of maternal deaths and stillbirths at the Hospital of Obstetrics and Gynecology at Wad Medani, Sudan, from 1 January 2003 through 31 December 2007. All maternal deaths and stillbirths during this period were reviewed and classified retrospectively. There were 146 maternal deaths and 33034 live births, giving a maternal mortality ratio of 442/100,000 live births. The age range was 18-42 years with a mean (standard deviation) of 30.57 (5.26) years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 3 publications
5
25
2
Order By: Relevance
“…Like our previous recent reports on maternal mortality in western and central Sudan, the causes of maternal mortality were similar in this hospital [1,2].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Like our previous recent reports on maternal mortality in western and central Sudan, the causes of maternal mortality were similar in this hospital [1,2].…”
Section: Discussionsupporting
confidence: 85%
“…There is wide regional and interregional variation in the causes of maternal death. Few data exist concerning maternal mortality in Sudan, which is the biggest African country with 40 million inhabitants [1,2]. Moreover, these were only reports without investigating the risk factors; there were no published data concerning maternal mortality in the eastern part of Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…That high frequency is comparable to those found by others authors working in the same situations: 2029 per 100,000 live births in Ivory Coast [8] and 2031 per 100,000 live births in Mali [9]. It is less elevated in some regions: Sudan 442 per 100,000 live births [10] and 92.6 per 100,000 live births in Algeria [11].…”
Section: Ampleness Of Maternal Mortalitysupporting
confidence: 86%
“…Sudan, the largest African country, has a high maternal mortality ratio with septicaemia, haemorrhage and obstructed labour as the main causes of deaths (Elhassan et al 2009) and the current study showed a high frequency of maternal morbidities. Like other reports in diff erent regions of Sudan, most of the women in this study had no antenatal care (Hassan et al 2009;Ali et al 2010).…”
Section: Discussionsupporting
confidence: 53%